Analisis Tingkat Penerimaan Dana Haji di Masa Pandemi Covid-19 - Irfan Ashari; Nabila Amalia; Kharis Fadlullah Hana (ISLAMIC BUSINESS and FINANCE, 2023)
The Pilgrimage is a worship that is a dream for all Muslims in the world, especially for the people of Indonesia where the majority of the population is Muslim.In a normal condition, financing is generally carried out regularly and in accordance with what has been planned, but the coming of a disaster is not the power of a personservant because only Allah can plan and will. The presence of a pandemicCovid-19 has caused changes in life patterns in all sectors. Therefore whether in During the Covid-19 pandemic, patterns and practices changed at the level Hajj funding. This type of research is field researchusing a qualitative phenomenological approach. The phenomena studied are:level of receipt of Hajj funds during the Covid-19 pandemic. Data collection techniques used in the form of interview techniques and collect data with techniques documentation. The results of the study show that prospective pilgrims during the Covid-19 pandemic19 experienced a significant decrease for several reasons, one of which was people choose umroh, because umroh does not take long. Hajj departure from Indonesia experienced reductions and delays during the covid-19 pandemic, hence from that some people prefer umroh to hajj because it is faster for timehis departure.